“Analysis The Productivity Of Heavy Equipment Cut And Fill Work” (Case Study: Package 6th Leuwikeris Dam Project Tasikmalaya-Banjar) - Yanto Yanto; Cornelia Gina Fransisca; Muhamad Decky Pambudi; Nikko Rozy (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
This research examines the productivity of heavy equipment used in the Cut and Fill work at the Leuwikeris Dam Project in Tasikmalaya, Indonesia. The study highlights the importance of efficient resource utilization and the environmental and social impacts associated with dam construction. A time study method was employed to analyze productivity, focusing on various heavy equipment such as excavators, dump trucks, bulldozers, and vibratory rollers. The findings indicate that factors such as equipment breakdowns, weather conditions, and material supply delays significantly impact productivity. The results aim to inform civil engineering practices and improve the understanding of heavy construction equipment efficiency in development projects.